Usaha Islah dan Tajdid Syed Syeikh al-Hadi menerusi karya "Hikayat Faridah Hanum" = The movement of reform (Islah) and renewal (Tajdid): Syed Sheikh al-Hadi in his novel "Hikayat Faridah Hanum - Yaacob, Adli; Faiz Hashim, Mohd Hafizul (Global Academic Excellence (M) Sdn Bhd (GAE), 2022)
Hikayat Faridah Hanim was regarded as the first Malay novel that introduced modern literature with meticulous writing and adaptation by Syed Syeikh al- Hadi. Besides the main topic of this study to discuss the characteristics of Islamic literary works, it also reveals the society's criticism with contemporary tone and their absorption of Muslim Middle Eastern movements. It also discusses further the efforts of the writer in reformation and modernization by pondering his delicate advises in each scene and his aesthetic language which all these affected Malay society.